Generalized subcutaneous emphysema secondary to perforating axillary wound in horse: Case report - Rodrigues, Luan; Estefanir Cordeiro, Amanda; Sucupira Júnior, Gerôncio; Formiga Leite, Rodrigo; da Silva Lima, Jorge Domingos (Pubvet, 2022)
Subcutaneous emphysema is considered as the accumulation of gas into the subcutaneous space and between the muscles bundles and fasciae. Subcutaneous emphysema in horses is rare and may be due to perforations of trachea and cutaneous tissue in regions of intense movement, resulting in air suction to the subcutaneous space. This report is a description of a 5-year-old Quarter Horse mare who suffered a perforating trauma at the axillary region due to the horning of a cattle. The animal was assisted at the Veterinary Hospital – Adílio Santos Azevedo (HV-ASA), from Instituto Federal da Paraíba – Campus Sousa, presenting generalized subcutaneous emphysema secondary to perforating wound which improved with antibiotic therapy, anti-inflamatory administration, daily wound cleaning and patient movement restriction. The animal discharged after 21 days. Thus, it was observed that secondary emphysema to skin wounds can have a good prognosis if treated correctly.